A scaffolding tool to assist learners in argumentative writing. Issue 1 (14th March 2021) - Fan, Cheng-Yu; Chen, Gwo-Dong
Abstract: Evidence indicates that graphic organizers, such as concept maps and argument maps, could help students develop a stronger argumentation ability and build effective argumentative structures. In this study, we designed a computer-aided argumentative essay writing system to assist students in learning structures of argumentation and in enhancing their argumentation abilities. In this study, an experiment was conducted on students in an elementary school in New Taipei City for fourteenth weeks. This included a total of 11 classes (272 students), which were divided into three groups: the argument map writing group, the concept map writing group, and the conventional argumentative writing group. The experimental results showed that the argumentative essays produced by the students in the argument map writing group were superior to those written by students in the other two groups.